STRATEGI ADAPTASI NELAYAN PANTAI SIBOLGA TERHADAP PERUBAHAN LINGKUNGAN WILAYAH PESISIR KOTA SIBOLGA, SUMATERA UTARA - Daud Daniel Hutapea; Yayat Dhahiyat; Sunardi Sunardi (Universitas Padjadjaran, 2014)
Adaptation strategies are responses from fishermen and fishing methods undertaken to obtain better results in fisheries activities. This strategy is believed to be a way to survive and can compete with other fishermen. On fishing communities, patterns of adaptation to adjust to the physical environment of marine ecosystems and the surrounding social environment. For people who work in the middle of the ocean, the ocean is the physical environment hazards. In many ways working in the marine environment laden with risk. Because fishermen are hunting for fish work, the results can not be determined certainty, everything is almost completely speculative. This study uses a mix of qualitative predominantly and quantitative less dominant. Qualitative methods are used to obtain in-depth information and coastal environmental change adaptation strategies Sibolga shore fishermen. Quantitative methods are used to obtain information characteristics of respondents fishing with size 87 samples taken from 65 households fisherman outboard motor boats and 22 fishing boats without motors households. Quantitative methods are also used to obtain data on changes in coastal environments. The analysis in the combined analysis methods using triangulation. Coastal environmental changes that occur are physical changes due to coastal Sibolga hoarding, residential additions and construction of buildings that affect the marine ecosystem fisheries; extent of decline of coral reefs, mangroves and seagrass beds caused, and a decline in quality of sea water in the surrounding waters Sibolga. Adaptation strategies Sibolga shore fishing can be divided into three aspects, namely social, economic and fishing techniques. Social adaptation strategy consists of social networks, mobilizing role of family members, changes in fishing group. Economic adaptation strategy consists of adding new gear, diversification of employment and capital management fishing. Adaptation strategies fishing technique consists of raising engine capacity ships, the use of technology, further the fishing area, adding to sea long, deepening the depth of fishing and the use of fishing tools.Keywords : Adaptation strategies fishermen, environmental change, coastal .